Sexual Dysfunction in Women Suffering from Gynecological Diseases - Nasimova Nigina Rustamovna; Jalalova Iroda Abduzhabborovna; Shamsieva Malika Shuxratovna (Zien Journals, 2023)
The analysis of long-term efficiency of operative treatment of pelvic prolapse for 213 women in periods ranging from 12 through questionnaire PISQ-12 (Pelvic Organ Prolapse and Incontinence Sexual Function Questionnaire), recommended for use in clinical practice of the international urogynaecologic Association and adapted by the authors for work . Method of evaluating the effectiveness of surgical treatment of pelvic and prostate has been streamlined through the introduction of a system of qualitative analysis of the results of the study of sexual function. Found that operational treatments pelvic prolapse have a positive effect on sexual function of women. Significant differences of sexual function in remote postoperative period depending on the type of operational benefits.The best effect with regard to the favourable dynamics of sexual function is achieved after laparoscopic operative treatment of pelvic prolapse compared with vaginal hysterectomy
Keywords: pelvic prolapse; surgery; remote effectiveness; sexual function